Impact of weighted average cost of capital (wacc) on utility‐scale solar photovoltaics (pv) levelized cost of electricity - Shendile, Severus Twahafa (University of the Witwatersrand, Johannesburg, 2023)
Namibia has one of the highest solar irradiation levels in the world, making it an ideal destination for renewable energy investments. The country receives an average of 300 days of sunshine per year. This means that there is an abundance of solar energy that can be harnessed for electricity generation using solar photovoltaic (PV) technology. The levelized cost of electricity (LCOE) is a key metric used to evaluate the financial viability of a solar PV project and is influenced by a range of factors that impact the cost of generating electricity from solar energy. The parameters that affect LCOE for solar PV systems include solar irradiation, O&M cost, financing cost, inverter efficiency, system design, system lifetime, regulatory environment, and the weighted average cost of capital. These parameters can interact with each other, and changes to one parameter can impact the LCOE in different ways. Several studies have considered the sun’s strength as the primary exogenous factor driving the cost of electricity and have treated other parameters such as the WACC, as largely endogenous and thus irrelevant to their analysis. This study has analyzed how the weighted average cost of capital from twenty- six projects in Namibia between 2014 -2022, impacts the levelized cost of electricity of utility-scale photovoltaic. This study has shown that while both solar irradiation and the WACC are essential factors that influence the LCOE of a solar PV project, WACC has a more significant impact on the LCOE for solar PV projects than solar irradiation because the cost of capital represents a substantial portion of the total cost of a solar PV project, while solar irradiation mainly affects the electricity generation potential of the project
A research report submitted in partial fulfillment of the requirements for the degree of Master of Management in Finance & Investment to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2023
Keywords: Solar irradiation; Renewable energy; Solar energy; Solar photovoltaic (PV) technology; Electricity; UCTD; SDG-7: Affordable and clean energy